From Chile to Israel: La muerte y la doncella by “Habima” Theatre (ALPHA. Journal of Arts, Literature and Philosophy, 1999)
In 1994, the Israeli National Theater produced Death and the Maiden by Ariel Dorfman.  The play presents the expectators with a private event through which the painful consequences of the years of Oppression and dictatorship on the members of the Chilean Society are revealed. Due to ample cultural differences between the two Nations, the production of display in Israel raises a series of questions concerning its potential relevancy for the Israeli local public and the range of adaptation it demands.That transformational process the play had to go through when put on that Israeli stage was made possible by the universal messages it contains, albiet its specific plot. such messages were detected by the stage director and his team and translated into such theatrical form which could be meaningful for the Israeli public.